2009
DOI: 10.1016/j.stem.2009.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Human Placenta Is a Potent Hematopoietic Niche Containing Hematopoietic Stem and Progenitor Cells throughout Development

Abstract: Hematopoietic stem cells (HSC) are responsible for the life-long production of the blood system and are pivotal cells in hematologic transplantation therapies. During mouse and human development, the first HSCs are produced in the aorta-gonad-mesonephros region. Subsequent to this emergence, HSCs are found in other anatomical sites of the mouse conceptus. While the mouse placenta contains abundant HSCs at midgestation, little is known concerning whether HSCs or hematopoietic progenitors are present and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(172 citation statements)
references
References 51 publications
(74 reference statements)
7
161
1
2
Order By: Relevance
“…Indeed, Zhang and colleagues have isolated mesenchymal progenitor cells from the human placenta that are capable of expanding long-term cultureinitiating cells from cord blood-derived CD34 + cells (Zhang et al 2004). We also have derived mesenchymal stromal cell lines from the human placenta (Robin et al 2009) and mouse placenta (I. Lauw, Master of Science thesis) from several stages of development. Some of these showed an extensive mesenchymal differentiation potential and also displayed a pericyte/perivascular cell phenotype similar to cells that have recently been reported to be the in vivo counterpart of mesesenchymal stromal/stem cells (Crisan et al 2008).…”
Section: Placenta Microenvironmentmentioning
confidence: 99%
“…Indeed, Zhang and colleagues have isolated mesenchymal progenitor cells from the human placenta that are capable of expanding long-term cultureinitiating cells from cord blood-derived CD34 + cells (Zhang et al 2004). We also have derived mesenchymal stromal cell lines from the human placenta (Robin et al 2009) and mouse placenta (I. Lauw, Master of Science thesis) from several stages of development. Some of these showed an extensive mesenchymal differentiation potential and also displayed a pericyte/perivascular cell phenotype similar to cells that have recently been reported to be the in vivo counterpart of mesesenchymal stromal/stem cells (Crisan et al 2008).…”
Section: Placenta Microenvironmentmentioning
confidence: 99%
“…All these approaches have suggested that discrete subsets of vascular ECs transiently exhibit blood-forming potential during vertebrate development. Recently a novel perspective to HSCs development came with the discovery that the human and murine placenta harbor a large pool of multipotential hematopoietic progenitors and stem cells, indicating that the placenta could play an important role in the establishment of hematopoiesis (Barcena et al, 2009;Robin et al, 2009;Mikkola et al, 2005; see also Ottersbach and Dzierzak; Mikkola, Dieterlen-Lièvre et al, in this issue). This process of HSCs emergence in the placenta is also intimately associated with large vessels (Rhodes et al, 2008) and therefore do highlight the role of vascular ECs in the generation of HSCs in vertebrates not only in the AGM, the umbilical and vitelline arteries but also in the placenta.…”
Section: Introductionmentioning
confidence: 98%
“…These hematopoiesis-potential mesoderm cells initiate primitive hematopoiesis after migrating to the yolk sac and can subsequently produce definitive hematopoietic cells [17,18]. The first definitive HSCs arise at the ventral wall of the dorsal aorta in the aorta-gonadmesonephros (AGM) region [19,20] and from murine and human placenta [21][22][23].…”
Section: Introductionmentioning
confidence: 99%